Infantile Pyknocytosis: An Uncommon Cause of Newborn Hemolytic Anemia. Issue 4 (May 2020) - Castillo, Jayme; Ness, Tara E.; Mehta, Parth S.
Abstract : Infantile pyknocytosis is a rare cause of neonatal hemolytic anemia, which presents in the first few weeks of life. We report a classic case of infantile pyknocytosis that presented to our institution with rebound hyperbilirubinemia after receiving phototherapy. The infant was found to have a hemoglobin of 5.8 g/dL, requiring a total of 15 mL/kg of red blood cells (in 2 separate transfusions) before discharge. The diagnosis was ultimately made by a review of the peripheral blood smear. We review the literature and suggest pediatricians consider infantile pyknocytosis on their differential when hemolytic anemia presents in the newborn period.